Polyolefin material as well as preparation method and application thereof
By adding a hyperbranched polyester with a specific amide group content to the polyethylene/polyolefin elastomer/inorganic filler system to form a lubricating layer, the existing low-smoke halogen-free cable materials have poor scratch resistance, low gloss or poor processing performance, and polyolefin materials with high gloss, good scratch resistance and good processing performance have been achieved.
Patent Information
- Application Number
- CN202411565264.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing low-smoke halogen-free cable materials have poor scratch resistance, low gloss or poor processing performance, making it difficult to meet the needs of high-performance cables.
By adding a specific amide group content to the polyethylene/polyolefin elastomer/inorganic filler system, a lubricating layer is formed to improve the scratch resistance and gloss of the material while improving the processing properties.
It significantly improves the gloss, scratch resistance and processing properties of polyolefin materials, and can meet the strict requirements of high-performance cables.
Smart Images

Figure BDA0005119053560000061 
Figure BDA0005119053560000062 
Figure BDA0005119053560000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material modification, and more specifically, to a polyolefin material and a preparation method and application thereof. Background Art
[0002] As the world pays more attention to environmental protection, the trend of low-smoke halogen-free cables replacing traditional PVC cables is becoming more and more obvious; in order to meet the performance requirements, low-smoke halogen-free cables generally adopt PE / EVA / POE / filler formula system, but the surface gloss and scratch resistance of this kind of high-filling, multi-resin alloy system after extrusion cannot reach the level of PVC cables. The annual market demand for low-smoke halogen-free cable materials is about 800,000 tons. The products are mainly used in home decoration and engineering construction wires, photovoltaic wires, automotive wires, power cables, communication cables, electrical appliances internal connection wires, optical fiber cables, etc., basically requiring good gloss and scratch resistance, especially for photovoltaic wires and automotive wires for export, which are transported over long distances, so surface scratch resistance is particularly important.
[0003] In order to meet the above stringent requirements, many manufacturers at home and abroad currently use PEEK materials as cable outer sheath materials, but this material is extremely expensive and requires special equipment for extrusion, which is extremely inconvenient to process. In addition, some manufacturers use the method of adding polyvinylidene fluoride (PVDF) or ultra-high molecular weight polyethylene (UHMWPE) to the existing formula system to improve the wear resistance of composite materials for cables, but due to the obvious melting point difference with the low-smoke halogen-free formula system, the effect of improving the scratch resistance of the finished cable is limited, and excessive addition will cause poor plasticization during the extrusion process.
[0004] Therefore, it is necessary to solve the problems of poor scratch resistance, low gloss or poor processing performance of current cable materials. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the problems of poor scratch resistance, low gloss or poor processing performance of the above-mentioned existing cable materials and to provide a polyolefin material.
[0006] A further object of the present invention is to provide a method for preparing the above polyolefin material.
[0007] A further object of the present invention is to provide use of the above polyolefin material in preparing cables.
[0008] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0009] A polyolefin material comprising the following components in parts by weight:
[0010] 10-20 parts of polyethylene,
[0011] 10-30 parts of polyolefin elastomer,
[0012] 40-60 parts of inorganic filler,
[0013] 3.5-9 parts of hyperbranched polyester;
[0014] The amide group content in the hyperbranched polyester is 5 to 10 wt %.
[0015] The inventors of the present invention have found through research that when a hyperbranched polyester containing a specific amide group content is added to the polyethylene / polyolefin elastomer / inorganic filler system, the polyester segment of the hyperbranched polyester has good compatibility with the formulation system of the present invention, and the amide group of the hyperbranched polyester is distributed on the surface of the polyolefin material to form a dense lubricating layer, thereby improving the scratch resistance of the polyolefin material, and the lubricating layer is also conducive to improving the gloss of the polyolefin material. In addition, the hyperbranched polyester itself can also play a lubricating role, improving the dispersibility and compatibility of each component during the material processing process, thereby improving the gloss and processing performance of the polyolefin material.
[0016] In the present invention, preferably, the content of polyethylene in the polyolefin material is at least 8 wt %.
[0017] Preferably, the polyethylene has a melt index of 1 to 7 g / 10 min under test conditions of 190° C. and 2.16 kg.
[0018] In the present invention, the melt index of the polyethylene can be measured according to GB / T 3682-2000.
[0019] Preferably, the polyolefin elastomer is at least one of ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer or ethylene-butyl acrylate copolymer.
[0020] Preferably, the polyolefin elastomer has a melt index of 0.5 to 10 g / 10 min under the test conditions of 190° C. and 2.16 kg.
[0021] In the present invention, the melt index of the polyolefin elastomer can be measured according to GB / T 3682-2000.
[0022] Preferably, the inorganic filler is a flame retardant inorganic filler.
[0023] More preferably, the flame retardant inorganic filler is at least one of aluminum hydroxide or magnesium hydroxide.
[0024] Preferably, the particle size D50 of the inorganic filler is 0.1-5 μm. The particle size D50 of the inorganic filler can be measured by a particle size analyzer.
[0025] In the present invention, the amide group of the hyperbranched polyester is a capping group.
[0026] In the present invention, the amide group content of the hyperbranched polyester refers to the mass percentage of CO-NH in the hyperbranched polyester. The amide group content of the hyperbranched polyester can be measured by elemental analysis, specifically: firstly measure the N element content of the hyperbranched polyester by an elemental analyzer, and then convert the N element content into the amide group content.
[0027] In the present invention, the hyperbranched polyester is formed by end-capping with an end-capping agent and a carboxyl-terminated hyperbranched polyester, and the carboxyl-terminated hyperbranched polyester is obtained by copolymerizing a triol and a dibasic acid; preferably, the end-capping agent includes but is not limited to methylamine, the triol includes but is not limited to propylene glycol, and the dibasic acid includes but is not limited to oxalic acid.
[0028] The preparation process of the hyperbranched polyester of the present invention is as follows: 40 to 80 parts by weight of triol and 90 to 130 parts by weight of dibasic acid are mixed, and polymerization reaction is carried out for 3 to 5 hours, and then methylamine is introduced for 4 to 6 minutes to obtain the hyperbranched polyester; the introduction rate of the methylamine is 0.06 to 0.12 mL / min.
[0029] Specifically, the polymerization reaction is carried out at 100-130° C.; the polymerization reaction is carried out in the presence of a catalyst, and the catalyst includes but is not limited to n-butyl titanate.
[0030] Preferably, the melting point of the hyperbranched polyester is 40-70°C.
[0031] More preferably, the melting point of the hyperbranched polyester is 60-65° C. By selecting the hyperbranched polyester within this melting point range, the obtained polyolefin material has higher gloss, better scratch resistance and better processing performance.
[0032] In the present invention, the content of the amide groups of the hyperbranched polyester may specifically be 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt% or 10 wt%.
[0033] Preferably, the content of amide groups in the hyperbranched polyester is 7.4-9 wt %. The hyperbranched polyester with the content of polyamide groups in this range is selected to obtain a polyolefin material with higher gloss, better scratch resistance and better processing performance.
[0034] Preferably, the polyolefin material further comprises 0.5 to 2 parts of other additives.
[0035] More preferably, the other auxiliary agent is at least one of an antioxidant or a lubricating auxiliary agent.
[0036] Further preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant DSTDP or antioxidant 1076.
[0037] Further preferably, the lubricating aid is at least one of silicone masterbatch, silicone oil or PE wax.
[0038] The method for preparing the polyolefin material comprises the following steps: mixing the components, melt-extruding, and granulating to obtain the polyolefin material.
[0039] Preferably, the temperature of the melt extrusion is 130-150° C.; the screw length-diameter ratio of the melt extruder is 35-45:1; and the screw speed is 400-500 r / min.
[0040] The use of the above polyolefin materials in the preparation of cables is also within the protection scope of the present invention.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] The polyolefin material of the invention has good glossiness, good scratch resistance and good processing performance. DETAILED DESCRIPTION
[0043] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0044] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0045] Polyethylene 1#: The melt index is 6g / 10min under the test conditions of 190℃ and 2.16Kg, brand LLDPE 7150, manufacturer Qilu Petrochemical;
[0046] Polyethylene 2#: The melt index is 1.9g / 10min under the test conditions of 190℃ and 2.16Kg, brand LDPE2420H, manufacturer CNOOC Shell;
[0047] Polyolefin elastomer 1#: EVA, melt index is 1g / 10min under the test conditions of 190℃ and 2.16Kg, EVA00320, Yangzi Petrochemical;
[0048] Polyolefin elastomer 2#: POE, melt index of 1.2 g / 10 min at 190°C and 2.16 kg, POELC168, LG Chem;
[0049] Inorganic filler 1#: magnesium hydroxide, particle size D50 = 0.1 μm, MDH-1, Yingkou, Liaoning;
[0050] Inorganic filler 2#: magnesium hydroxide, particle size D50 = 3 μm, MDH-2, Yingkou, Liaoning;
[0051] Inorganic filler 3#: aluminum hydroxide, particle size D50 = 4 μm, ATH-1, China Aluminum Corporation;
[0052] Other additives 1#: antioxidant 1010, commercially available;
[0053] Hyperbranched polyester 1#: self-made, the preparation process is as follows: add 60 parts by weight of propylene glycol, 110 parts by weight of oxalic acid, and 0.5% of n-butyl titanate based on the total weight of acid and alcohol into a reaction kettle, react at 120°C for 4 hours (recorded as time t), then introduce methylamine for 5 minutes, and the rate of methylamine introduction is 0.1mL / min; remove the water produced by the reaction, cool to room temperature, and obtain a reaction product. The obtained reaction product is vacuum dried for 2 hours to obtain a hyperbranched polyester; the content of amide groups in hyperbranched polyester 1# is 7.5wt%, and the melting point is 60°C.
[0054] Hyperbranched polyester 2#: self-made, the difference from hyperbranched polyester 1# is that the methylamine introduction rate is 0.06 mL / min. The content of amide groups in hyperbranched polyester 2# is 6 wt%, and the melting point is 60°C.
[0055] Hyperbranched polyester 3#: self-made, the difference from hyperbranched polyester 1# is that the methylamine introduction rate is 0.12 mL / min. The content of amide groups in hyperbranched polyester 3# is 8.5 wt%, and the melting point is 60°C.
[0056] Hyperbranched polyester 4#: self-made, the difference from hyperbranched polyester 1# is that the reaction time t is 3 hours. The content of amide groups in hyperbranched polyester 4# is 7.4 wt%, and the melting point is 45°C.
[0057] Hyperbranched polyester 5#: self-made, the difference from hyperbranched polyester 1# is that the reaction time t is 5 hours. The content of amide groups in hyperbranched polyester 5# is 7.7 wt%, and the melting point is 65°C.
[0058] Hyperbranched polyester 6#: self-made, the difference from hyperbranched polyester 1# is that the methylamine introduction rate is 0.03 mL / min. The content of amide groups in hyperbranched polyester 6# is 3 wt%, and the melting point is 60°C.
[0059] Hyperbranched polyester 7#: self-made, the difference from hyperbranched polyester 1# is that methylamine is not introduced. Hyperbranched polyester 7# does not contain amide groups and has a melting point of 60°C.
[0060] Non-hyperbranched polyester 8#: self-made, the difference from hyperbranched polyester 1# is that 60 parts by weight of ethylene glycol and 110 parts by weight of oxalic acid are added. The content of amide groups in non-hyperbranched polyester 8# is 2 wt%, and the melting point is 55°C.
[0061] Hyperbranched polyester 9: a vinyl terminated hyperbranched polyester, homemade, and the difference from hyperbranched polyester 1# is that methylamine is replaced by acryl alcohol to prepare a vinyl terminated hyperbranched polyester. The vinyl content of hyperbranched polyester 9 is 7.4 wt%, and the melting point is 59°C.
[0062] Hyperbranched polyamide: HyPer N101, Wuhan Hyperbranched Resin Technology Co., Ltd.
[0063] Unless otherwise specified, the components (such as other auxiliary agent 1#) selected in each parallel example and comparative example are the same commercially available products.
[0064] The polyolefin materials provided in the embodiments and comparative examples of the present invention were tested for performance according to the following test methods:
[0065] (1) Glossiness: Heat the double-roll mill to 120°C. After the temperature stabilizes, place the material in the double-roll mill and mix for about 5 minutes before discharging the sheet. Then preheat the sheet in a flat fluidizer at 180°C without pressure for 5 minutes, heat and pressurize for 5 minutes, and then cool to room temperature before discharging the sheet. The pressure is set at 13MPa. The 1mm thick sheet discharging the sheet should be flat, smooth, uniform in thickness, and free of bubbles. The glossiness is measured by a non-contact gloss meter YG60L.
[0066] (2) Scratch resistance: The double-roll mill is heated to 120°C. After the temperature stabilizes, the material is placed in the double-roll mill and mixed for about 5 minutes before being discharged. The material is then preheated in a flat fluidizer at 180°C without pressure for 5 minutes, then heated and pressurized for 5 minutes, and then cooled to room temperature for discharge. The pressure is set at 13MPa. The 1mm thick test piece discharged from the mold should be flat, smooth, uniform in thickness, and free of bubbles. The scratch resistance is measured by a cross scratch tester. The scratch depth is used to indicate the scratch resistance. The smaller the scratch depth, the better the scratch resistance.
[0067] (3) Processing performance: The maximum line speed that can be achieved during extrusion is used to characterize the quality of the processing performance. The criterion for judgment is that at this maximum line speed, the finished wire does not have wire diameter fluctuations and the surface has no appearance defects.
[0068] The polyolefin materials provided in the embodiments and comparative examples of the present invention are prepared as follows:
[0069] Weigh each component according to the formula, then add it to the twin-screw extruder from the main feed, and obtain the polyolefin material through melt extrusion and granulation; wherein the screw length-diameter ratio of the twin-screw extruder is 40:1; the screw speed is 350r / min, and the melting temperature is 130-150°C.
[0070] Examples 1 to 13
[0071] Examples 1 to 13 provide a series of polyolefin materials, and their formulations are shown in Table 1.
[0072] Table 1 Formulas of Examples 1 to 13 (parts by weight)
[0073]
[0074] Comparative Examples 1 to 7
[0075] Comparative Examples 1 to 7 provide a series of polyolefin materials, the preparation methods of which are substantially the same as those of Example 1, and the formulations thereof are shown in Table 2.
[0076] Table 2 Formulas of Comparative Examples 1 to 7 (parts by weight)
[0077]
[0078]
[0079] The properties of the polyolefin materials of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 3.
[0080] Table 3 Performance results of various embodiments and comparative examples
[0081]
[0082]
[0083] From Table 3, we can see that:
[0084] The glossiness of the polyolefin materials of Examples 1 to 13 is all above 90, the scratch depths in the scratch resistance test are all below 30 μm, and the maximum line speeds in the processing performance test are all above 150 m / min, indicating that the polyolefin materials of the present invention have good glossiness, good scratch resistance and good processing performance.
[0085] Comparative Example 1 adds medium acid amide, and the gloss of the obtained polyolefin material is low, the scratch resistance cannot be well improved, and the processing performance is also poor. The amide group content of the hyperbranched polyester added in Comparative Example 2 is too low, and the gloss of the obtained polyolefin material is not good, and the scratch resistance cannot be well improved. The hyperbranched polyester added in Comparative Example 3 does not contain amide groups, and the gloss of the obtained polyolefin material is not good, and the scratch resistance cannot be well improved. Comparative Example 4 adds non-hyperbranched polyester, and the performance of the obtained polyolefin material is equivalent to the situation of adding medium acid amide. Comparative Example 5 does not add hyperbranched polyester, and the various properties of the obtained polyolefin material are poor. Comparative Example 6 adds vinyl-containing hyperbranched polyester, and the gloss of the obtained polyolefin material is low, and the scratch resistance cannot be well improved. Comparative Example 7 adds hyperbranched polyamide, and the various properties of the obtained polyolefin material are poor.
[0086] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polyolefin material, characterized in that: The composition comprises the following components in parts by weight: The amide group content in the hyperbranched polyester is 5 to 10 wt %.
2. The polyolefin material according to claim 1, characterized in that: The polyethylene has a melt index of 1-7 g / 10 min under the test conditions of 190° C. and 2.16 kg.
3. The polyolefin material according to claim 1, characterized in that: The polyolefin elastomer is at least one of ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer or ethylene-butyl acrylate copolymer.
4. The polyolefin material according to claim 1, characterized in that: The inorganic filler is a flame retardant inorganic filler.
5. The polyolefin material according to claim 1, characterized in that: The particle size D50 of the inorganic filler is 0.1 to 5 μm.
6. The polyolefin material according to claim 1, characterized in that: The melting point of the hyperbranched polyester is 40-70°C.
7. The polyolefin material according to claim 1, characterized in that: The amide group content of the hyperbranched polyester is 7.4-9 wt %.
8. The polyolefin material according to claim 1, characterized in that: The polyolefin material also includes 0.5 to 2 parts of other additives.
9. The method for preparing the polyolefin material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the components, melt-extruding and granulating to obtain the polyolefin material.
10. Use of the polyolefin material according to any one of claims 1 to 8 in the preparation of cables.
Citation Information
Patent Citations
Hyperbranched polyester and synthesis method thereof and thermoplastic resin composite and preparing method thereof
CN110172141A
Hyperbranched polyester and synthesis method thereof as well as thermoplastic resin composite material and preparation method thereof
CN110294897A
Hyperbranched polyester, synthesis method thereof, thermoplastic resin composition and preparation method of thermoplastic resin composition
CN110885433A
HDPE-g-GMA modified polypropylene composite material, preparation method and application thereof
CN113980386A
High-flexibility and high-flame-retardant elastomer cable material capable of resisting high temperature of 150 DEG C as well as preparation method and application thereof
CN115028919A